2012
DOI: 10.2147/ijn.s29506
|View full text |Cite
|
Sign up to set email alerts
|

PLGA nanoparticle-mediated delivery of tumor antigenic peptides elicits effective immune responses

Abstract: Abstract:The peptide vaccine clinical trials encountered limited success because of difficulties associated with stability and delivery, resulting in inefficient antigen presentation and low response rates in patients with cancer. The purpose of this study was to develop a novel delivery approach for tumor antigenic peptides in order to elicit enhanced immune responses using poly(DL-lactide-co-glycolide) nanoparticles (PLGA-NPs) encapsulating tumor antigenic peptides. PLGA-NPs were made using the double emulsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
85
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 56 publications
10
85
1
Order By: Relevance
“…1C). This result was in agreement with extensive prior studies, which showed that PLGA particles from 50 nm to 3 μm in size could be effi ciently taken up by DCs (KovacsovicsBankowski and Rock, 1995;Ma et al, 2012).…”
supporting
confidence: 92%
See 4 more Smart Citations
“…1C). This result was in agreement with extensive prior studies, which showed that PLGA particles from 50 nm to 3 μm in size could be effi ciently taken up by DCs (KovacsovicsBankowski and Rock, 1995;Ma et al, 2012).…”
supporting
confidence: 92%
“…(Kovacsovics-Bankowski and Rock, 1995;Zhang et al, 2011;Ma et al, 2012). PLGA particles can protect the antigen from enzymatic degradation (Kovacsovics-Bankowski and Rock, 1995), increase the effi ciency of antigenloading (Hanlon et al, 2011;Ma et al, 2012), facilitate cross-presentation of the antigen (Ma et al, 2011), and co-deliver adjuvant into DCs (Zhang et al, 2007). In agreement with these immune-modulating mechanisms of PLGA carriers, we also observed that PLGA MPs could be effectively taken into the cytoplasm of DCs (Fig.…”
supporting
confidence: 75%
See 3 more Smart Citations